Inertia I: The Global MSp-SUSY Induced Uniform Motion - Ter-Kazarian, G.
In this communication our main emphasis is on the review of the foundations of standard Lorentz code (SLC) of a particle motion. To this aim, we develop the theory of global, so-called, `double space´- or master space (MSp)-supersymmetry, subject to certain rules, wherein the superspace is a 14D-extension of a direct sum of background spaces M4⊕ MSp by the inclusion of additional 8D fermionic coordinates. The latter is induced by the spinors θ and ¯θ referred to MSp. While all the particles are living on M4, their superpartners can be viewed as living on MSp. This is a main ground for introducing MSp, which is unmanifested individual companion to the particle of interest. Supersymmetry transformation is defined as a translation in superspace, specified by the group element with corresponding anticommuting parameters. The multiplication of two successive transformations induce the motion. As a corollary, we derive SLC in a new perspective of global double MSp-SUSY transformations in terms of Lorentz spinors (θ, ¯θ). This calls for a complete reconsideration of our ideas of Lorentz motion code, to be now referred to as the individual code of a particle, defined as its intrinsic property. In MSp-SUSY theory, obviously as in standard unbroken SUSY theory, the vacuum zero point energy problem, standing before any quantum field theory in M4, is solved. The particles in M4 themselves can be considered as excited states above the underlying quantum vacuum of background double spaces M4⊕ MSp, where the zero point cancellation occurs at ground-state energy, provided that the natural frequencies are set equal (q2 0 ≡ νb = νf ), because the fermion field has a negative zero point energy while the boson field has a positive zero point energy. On these premises, we derive the two postulates on which the Special Relativity (SR) is based.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture